Depenalization of Drug Abuse Criminal Act as a Humanist Criminal Law Policy - R.B. Muhammad Zainal Abidin (Faculty of Law, Universitas Airlangga, 2024)
The purpose of this research is to analyze and evaluate ratio legis of criminal sanctions against perpetrators of narcotics abuse and policy reformulation of humanist sanction arrangements against narcotics abusers in the future. This research is a legal research that uses statutory and conceptual approaches. The results of study; (1) ratio legis of providing criminal sanctions against narcotics abusers as referred to in Act Number 35 Year 2009 concerning Narcotics is that the formers of the Act still adhere to the retrebutive paradigm. The target of rehabilitation is only limited to victims of drug abuse, not drug abusers; (2) the policy reformulation of sanctions against drug abusers in the future is no longer using criminal law means. The means used are non-penal means that remove criminal sanctions and replace them with rehabilitation measures.